Neo-colonialism In Music Therapy: A Critical Interpretive Synthesis of the Literature Concerning Music Therapy Practice With Refugees - Comte, Rachael (Voices: A World Forum for Music Therapy, 2016)
This paper presents the findings from a critical interpretive synthesis that explored the assumptions influencing music therapists writing about their work with refugees. Music therapy literature suggests that the profession appears to be uniquely suited to address the healthcare needs of the refugee population by transcending cultural and language barriers which often mitigate access to other services. However, when working with individuals characterised by trauma and whose identities have been dictated by political power, it is essential that music therapy practices oppose these forces and provide opportunities for empowerment. Therefore, eleven papers describing music therapy practice with refugees from the international literature were examined and interrogated to determine the assumptions embedded within the language used by music therapists. The synthetic construct of a neo-colonial music therapist emerged from the data and informed subsequent analysis. The concepts of refugees as a homogenous group defined by a dominant narrative of trauma, and musical improvisation as a universal language appeared to be influential in the ways music therapists were reporting on their work. These findings are discussed along with considerations for a music therapy practice that promotes empowerment and advocates for the voices of the refugee population.